2018
DOI: 10.1007/s00335-018-9752-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of cerebral malaria in the mouse model infected with Plasmodium berghei

Abstract: Malaria is a common and sometimes fatal disease caused by infection with Plasmodium parasites. Cerebral malaria (CM) is a most severe complication of infection with Plasmodium falciparum parasites which features a complex immunopathology that includes a prominent neuroinflammation. The experimental mouse model of cerebral malaria (ECM) induced by infection with Plasmodium berghei ANKA has been used abundantly to study the role of single genes, proteins and pathways in the pathogenesis of CM, including a possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 211 publications
1
32
1
Order By: Relevance
“…2,5 Mutations that affect the number of function of these cells result in partial or complete protection against lethality in the P. berghei infection model. 4 As opposed to control ECM-susceptible B6 mice, the recruitment of proinflammatory myeloid cells (including DCs) to the CNS is not seen in ECM-resistant Ccdc88b mutants. 7 The impaired migratory properties of Ccdc88b Mut DCs established in the present study suggests a causal relationship with the ECM protection phenotype of mutant mice.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…2,5 Mutations that affect the number of function of these cells result in partial or complete protection against lethality in the P. berghei infection model. 4 As opposed to control ECM-susceptible B6 mice, the recruitment of proinflammatory myeloid cells (including DCs) to the CNS is not seen in ECM-resistant Ccdc88b mutants. 7 The impaired migratory properties of Ccdc88b Mut DCs established in the present study suggests a causal relationship with the ECM protection phenotype of mutant mice.…”
Section: Discussionmentioning
confidence: 96%
“…3 The mouse model of experimental cerebral malaria (ECM) induced by infection with Plasmodium berghei ANKA discovered a number of genes in which inactivation causes ECMresistance in PbA-infected mice. 6,7,4,8,9 One of these, Ccdc88b, encodes a poorly annotated protein (also known as Gipie, HkRP3), that belongs to the hook-related protein family shown to have a role in microtubuledependent organelle and endosomal vesicle movement. 10 Ccdc88b…”
Section: Introductionmentioning
confidence: 99%
“…Given that ThPOK is a transcription factor expressed in thymocytes (29) and that the R367Q mutation is likely to affect DNA binding, we aimed to systematically identify the genes bound (cistrome) and possibly regulated by ThPOK and whose altered expression may underlie the altered inflammatory response phenotype of mutant mice. We prepared chromatin from Th1 polarized CD4 ϩ T cells, a cell type known to be a major driver of pathological neuroinflammation in the ECM model (8), and conducted ChIPseq. We found that ThPOK is recruited to 6,314 genomic sites and that ϳ73% of those sites are within 5 kb of a gene transcriptional start site ( Fig.…”
Section: Figmentioning
confidence: 99%
“…Although the P. berghei ANKA mouse model does not reproduce all facets of human CM, there are several aspects of disease pathogenesis and host immune response that are common to both. The shared features include (i) rapidly progressing neurological symptoms, such as convulsions, paralysis, seizures, and coma; (ii) histopathology, including vascular obstruction, parenchymal hemorrhage, and weakening of the blood-brain barrier; (iii) sequestration of parasitized erythrocytes (pRBCs); (iv) overlapping host immune and inflammatory responses, including a key role of infiltrating monocytes, T cells, and platelets at the site of injury, astroglial activation, and upregulation of antigen presentation molecules (e.g., major histocompatibility complex class 1 [MHC-I] and MHC-II) and of host endothelial adhesion molecules (e.g., ICAM-1) on cerebral vessels (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
See 1 more Smart Citation